The ancient magus' bride. Volume 17 - Yamazaki, Kore (Seven Seas Entertainment, 2023)
The reflection of a false god has manifested. Is it the Testament? Or is it still Philomela? The conglomeration that they've become seeks to leave the College, making for the banquet hall where the College faculty celebrates. Chise and Elias burst into a tense situation, and find themselves having to face off against both sides."--Back cover.